DESIGN OF SOLAR PHOTOVOLTAIC SYSTEM AT LANGUAGE CENTER OF TANJUNGPURA UNIVERSITY USING PVSYST - anto, Timotius Ari; Hasan, Yandri; Hiiendro, Ayong (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2023)
West Kalimantan is widely available new renewable energy sources (RES) in the form of sufficient solar energy potential to become a Solar Power Plant (SPP) especially for areas that have high solar potential, such as in Pontianak which is located on the equator then, This study evaluates the Solar Power Plant which is located at the UPT Language of Tanjungpura University, Southeast Pontianak District, Pontianak City. The tool used to help solve the problems in this study is the PVsyst software. This tool is used to analyze the planning of SPP. The total load of electrical energy used consists of 6 electronic devices which is often used at the UPT Language of the University of Tanjungpura per day is 80,584 kWh/day, and for the need for electrical energy for 1 year of 29.010 kWh/year. For the results of energy production by a panel with a nominal capacity of 22 kW which is capable of producing a total energy of 32.904 kWh/year. From the results of the economic analysis in this study, the total NPV was obtained Rp.397.823.869, LCC Rp.555.807.731 for a COE of  Rp.1.478/kWh for maintenance and operational costs of  Rp.4.928.090,and Discount Payback Periode (DPP) 15,1 year is the result of 25 years of economic analysis obtained from the PVsyst software simulation source.